Pitfalls in the Modelling of Forward-Looking Price Setting and Inverstment Behavior - Tommy Sveen; Lutz Weinke (Norges Bank, 2004)
We discuss some difficulties in a dynamic New-Keynesian model with staggered price setting al̀a Calvo and a convex capital adjustment cost at the firm level, as considered by Woodford (2003, Ch. 5). It is shown that the implied simultaneous price setting and investment decision has not been analyzed properly. Our work fills that gap by proposing a tractable solution to the key problem of describing the inflation dynamics associated with that structure. We use our framework to assess to what extent capital accumulation matters for inflation and output dynamics.
hdl:11250/2498551
Keywords: E22; E31; 330; sticky prices; investments